Keutamaan Memelihara Kucing dalam Perspektif Islam: Studi Takhrij dan Syarah Hadis - Akbar, Muhammad Faizhil (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
This study has the aim of discussing the hadith about the dangers of keeping a cat by not caring for it properly or mistreating it such as locking it up by not giving it food and water. This study uses a qualitative method through a literature study applying the takhrij and syarah hadith methods through contemporary analysis. The result of this research is that the quality of the hadith about the dangers of keeping a cat by molesting it is found to be authentic according to the consensus of scholars and the results of a research review. With the rise of the cat lover community today, it is very helpful in increasing awareness of cats as well as providing education to the public. As we know cats are the favorite pets of the Prophet Muhammad SAW, because cats are not only cute, they are also clean and free from unclean animals, in Islam it is legal to keep a cat. Of the several virtues of keeping a cat, one of them is an activity that is favored by Allah SWT. There are conclusions that can be drawn from this research, namely increasing our concern for cats in maintaining them and freeing them from hunger or thirst, which are found in our environment.